Social Capital in Education - Stanislaw Walukiewicz; Aneta Wiktorzak (European Regional Science Association (ERSA), 2010)
We consider education, and the final stage of secondary education in particular, as a number of creative processes and analyse two of them in detail: teaching knowledge/subjects (process P1) and teaching skills (process P2). In part 1 we describe the idea of Virtual Production Line (VPL), introduced by Walukiewicz in 2006 as an extension of Classical Production Line (CPL), an epitome of our perception of Henry Ford's assembly line. Teachers connected by modern ICT network (in most cases it will just be the Internet) provide education to students on a VPL - kind of a virtual belt - instructing a given set of subjects (tasks) in a prescribed sequence, offering teaching load using a prescribed methodology, etc. In contrast to CPL, teachers on VPL will use their brains mostly and divide the teaching process into a number of tasks in what we will call 'self-organization of VPL'. In that perspective VPL shall be defined as a conscious experience of a division of labour into tasks (self-organization) involving the Internet, while CPL will just remain a partition of labour into a fixed number of jobs. In part 2 we discuss P2 process. We claim that its efficiency depends heavily on social capital of a given school (cooperation of teachers, trust, etc.) Again, we will use VPL as a tool to perform necessary measures. We study the transition from P1 to P2. We will introduce a problem of optimal assignment of teachers to tasks using the concept of cognitive and emotive proximity. In conclusion, we formulate suggestions for further research
Keywords: 330